2007
DOI: 10.1111/j.1445-2197.2007.04227.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Parathyroidectomy Using Surgeon‐performed Ultrasound and Sestamibi

Abstract: SPU in the hands of an experienced surgeon in association with sestamibi is a reliable tool for the preoperative localization of parathyroid adenomas and facilitates a minimally invasive procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…In all studies, diagnosis was confirmed by successful surgical removal of parathyroid pathology with or without post surgical follow up histology and blood assays. Five studies additionally confirmed surgical success with follow up assays (Bhansali et al 2006;Carlier et al 2008;Lo et al 2007;Prasannan et al 2007;Shaheen et al 2008), and three studies confirmed the nature of the excised lesion(s) with histology (Mihai et al 2006;Lo et al 2007;Carlier et al 2008). …”
Section: Medline Via Ovidspmentioning
confidence: 87%
See 4 more Smart Citations
“…In all studies, diagnosis was confirmed by successful surgical removal of parathyroid pathology with or without post surgical follow up histology and blood assays. Five studies additionally confirmed surgical success with follow up assays (Bhansali et al 2006;Carlier et al 2008;Lo et al 2007;Prasannan et al 2007;Shaheen et al 2008), and three studies confirmed the nature of the excised lesion(s) with histology (Mihai et al 2006;Lo et al 2007;Carlier et al 2008). …”
Section: Medline Via Ovidspmentioning
confidence: 87%
“…All studies, except two, (Mihai et al 2009, Prasannan et al 2007) stated that the US was interpreted without knowledge of the results of the NM scan. While, this approach limits risk of contamination between the two localization studies and provides an independent assessment of the localization study's performance, it does not mirror usual clinical practice.…”
Section: Medline Via Ovidspmentioning
confidence: 99%
See 3 more Smart Citations